PENGARUH PEMANFAATAN SISTEM INFORMASI AKADEMIK (SISKA) TERHADAP KINERJA INDIVIDUAL DENGAN KEGUNAAN PERSEPSIAN SEBAGAI VARIABEL MODERATING - Aulia, Dwi Himma; Widijoko, Grace (Jurnal Ilmiah Mahasiswa FEB, 2013)
The objective of research  is  to understand  the  influence of  the use of academic information  system  (SISKA  =  sistem  informasi  akademik)  on  individual  performance with  the  perceived  useful  as  the  moderating  variable.  Research  population  includes employees  of  Faculty  of  Economic  and  Business,  University  of  Brawijaya  Malang, which the total is 112 respondents. Sampling method is purposive sampling.   All  population  members  meet  sample  criteria,  but  the  sample  is  only  those meeting research criteria. The employee who has used SISKA  is 45  freelances and 67 civil servants. The sample which meets criteria is counted to 71 respondents. Data are collected through questionnaire. The questionnaire has been examined with  reliability  and  validity  tests.  The  classical  assumption  test  includes  multi-collinearity  test, normality  test and heteroscedasticity  test. Hypothesis  test  is  followed by T-test.   Result of research indicates that the variable of the use of academic information system  (SISKA)  has  positive  and  significant  impact  on  individual  performance.  the variable  of  perceived  useful  is  moderating  the  variable  of  the  use  of  academic information  system  (SISKA) which  is  then  influencing  individual  performance,  and  in such that, the variable of perceived useful represents the moderating variable. Keywords: The Use of Information System, Perceived Useful, Individual Performance